If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x(x) + -5x + 53 = 119 Multiply x * x x2 + -5x + 53 = 119 Reorder the terms: 53 + -5x + x2 = 119 Solving 53 + -5x + x2 = 119 Solving for variable 'x'. Reorder the terms: 53 + -119 + -5x + x2 = 119 + -119 Combine like terms: 53 + -119 = -66 -66 + -5x + x2 = 119 + -119 Combine like terms: 119 + -119 = 0 -66 + -5x + x2 = 0 Factor a trinomial. (-6 + -1x)(11 + -1x) = 0Subproblem 1
Set the factor '(-6 + -1x)' equal to zero and attempt to solve: Simplifying -6 + -1x = 0 Solving -6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + -1x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 0 + 6 -1x = 0 + 6 Combine like terms: 0 + 6 = 6 -1x = 6 Divide each side by '-1'. x = -6 Simplifying x = -6Subproblem 2
Set the factor '(11 + -1x)' equal to zero and attempt to solve: Simplifying 11 + -1x = 0 Solving 11 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 0 + -11 -1x = 0 + -11 Combine like terms: 0 + -11 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11Solution
x = {-6, 11}
| z+6=-5 | | 3x^3+11x^2=-6x | | 12x^3+23x^2-9x=0 | | 2x^2+x-10=0 | | -4y+3=19 | | 4-2b=-8 | | 4d+5=85 | | 5-7x=47 | | 3x+5(4x-6)-8=3x-14 | | 10x-15=5(x+81) | | -2x+3x-6=4x+8 | | 10p+4=1 | | x^2+y^2-(4k+3)y=0 | | 2x+0.5x=40500 | | 8r-(6r+10)=8 | | 10x-25=5x+50 | | -2x=-5 | | (1+k)x^2+(1+k)y^2-(k+9)x-2(5k-1)y+9k+5=0 | | -6x-15=-x-55 | | 6-3x=-x+1 | | 11+8x=2-3x | | 3+4(x+4)=159 | | 3p+4q=33 | | 10p+12q=102 | | x^2-x+1=0 | | 4x+20=-6(x-25) | | 7x-2=5-x | | 10q=80 | | 59=a+48 | | 47-s=42 | | 85=3+z | | m-14=9 |